2017
DOI: 10.1155/2017/3507124
|View full text |Cite
|
Sign up to set email alerts
|

Real World Evidence: A Quantitative and Qualitative Glance at Participant Feedback from a Free-Response Survey Investigating Experiences of a Structured Exercise Intervention for Men with Prostate Cancer

Abstract: Aim To explore patient experiences of a structured exercise intervention for men with prostate cancer (PCa). Sample 41 men with either localised or advanced PCa who had been referred for a structured exercise programme by their physician and then subsequently consented to a telephone survey. Method Participants underwent a 10-week supervised exercise programme within a large cancer centre hospital consisting of 8 sessions. They then completed a short multiple choice telephone survey, elaborating on their respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…Participants valued the supervised, individualized, and gradual progression of the exercise component of the intervention and the study trainers' support. In agreement with previous studies, supervised exercise, trainer support, and individualization are common facilitators in exercise interventions 25‐27 . On the other hand, lack of individualization and unchallenging exercises are reported as barriers to intervention adherence 27,28 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Participants valued the supervised, individualized, and gradual progression of the exercise component of the intervention and the study trainers' support. In agreement with previous studies, supervised exercise, trainer support, and individualization are common facilitators in exercise interventions 25‐27 . On the other hand, lack of individualization and unchallenging exercises are reported as barriers to intervention adherence 27,28 .…”
Section: Discussionsupporting
confidence: 87%
“…This theme is also apparent in a BCS diet and exercise trial by Balneaves et al, where participants recommended having a program partner or a modified version for a partner to do at home to provide support and reinforcement of the acquired habits 22 . Lack of companionship is additionally a reported barrier in other exercise interventions 19,26 . Group exercising and support from other study members increases motivation and facilitates exercising, and therefore should be encouraged in future exercise interventions 22,26‐28 .…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to our knowledge that compares both aerobic and resistance exercise levels of prostate cancer survivors with exercise preferences, barriers and facilitators. Similar to previous research, the majority of study participants were interested in participating in a structured exercise programme (Forbes et al, , ; Fox et al, ; Harrington et al, ; McGowan et al, 2013). In contrast to previous finding by Forbes et al (, ), who found prostate cancer survivors preferred home‐based exercise and walking, our participants had a strong preference for participating in exercise from a community‐based gym setting (community centre, YMCA, leisure centre or local gym) and home‐based setting.…”
Section: Discussionmentioning
confidence: 86%
“…It helps accelerate evidence generation through providing observational studies that can generate new hypotheses and support policy makers. Prior to its formal development, a wide variety of studies had already been published using the clinical data of GSTT's cancer patients (based on individual ethics or audit approval) including various studies focused on prostate cancer [4][5][6][7][8][9], breast cancer [10][11][12][13] and renal cancer [14]. The below case study shows how data from Guy's Cancer Cohort was used to address a clinically important question for bladder cancer:…”
Section: Utility and Discussionmentioning
confidence: 99%